Function of the Promoter of PSPAL2, a Pea Defensive Gene Encoding Phenylalanine Ammonia-lyase - Permpong Sriprasertsak; Anchalee Raweerotwiboon; Tetsuji Yamada; Thira Sutrabutra (Agriculture and Natural Resources, 2002)
The phenylalanine ammonia-lyase is a key enzyme in phenylpropanoid synthesis, a pathway for the biosynthesis of a wide range of natural products which play key roles in plant development and protection against environmental stresses including the structural polymer lignin, flavonoids (anthocyanin pigments and UV protectants), isoflavonoids and phytoalexins. In this study, PSPAL2, a member of pea PAL gene family was determined and structurally characterized. The structure of PSPAL2 was divided into two exons by the single intron of 90 bp. In PSPAL2, some putative cis-regulatory elements of box I, box II, and box IV conserved among the promoter of several genes involved in the phenylpropanoid pathway and the retrotransposon-like sequences were found in the 5/-upstream region of PSPAL2 promoter. To discriminate the function of PSPAL2 promoter, the expression of pea PSPAL2 retrotransposonlike sequence in the region between –406 and –2196 and the three types of sequentially deleted chimeric promoter constructs designated as PSPAL2-FLd1, PSPAL2-FLd2 and PSPAL2-FLd3 in transgenic tobacco during developmental growth and upon fungal ingression were demonstrated. The histochemical GUS expression in young seedlings and mature plants were found in tissue and specific organs (roots, stems, leaves, flower organs and anthers). Moreover, the levels of GUS activities in tissues of transgenic plants depending on the 5/-upstream region of PSPAL2 promoter were also determined. Extremely low GUS expression was observed in healthy or undisturbed mature leaves. However, the PSPAL2promoter activated in the leaves of transgenic tobacco plants after transferring to the greenhouse was induced upon fungal ingression, especially when the leaves were inoculated with P. capsici and incubated at 22-24°C for 48 hr. Marked expression was detected at the HR area surrounding the inoculation site of the transformant of PSPAL2-FL. Extremely low GUS expression was observed in the transformant of PSPAL2-FLd3. The results demonstrated that the region from –966 to –2196 of PSPAL2 promoter played a crucial role in the regulation of induction of GUS activities in the mature leaves of transgenic tobacco plants. It was thus clear that the 5/-upstream region between +110 to –594 was insufficient to establish the full capacity of defense gene response under stress even though this region contained important box sequences such as box I, box II and box IV.